Functional brain connectivity from EEG in epilepsy: Seizure prediction and epileptogenic focus localization - van Mierlo, Pieter; Papadopoulou, Margarita; Carrette, Evelien; Boon, Paul; Vandenberghe, Stefaan; Vonck, Kristl; Marinazzo, Daniele (Progress in Neurobiology, 2014)
Today, neuroimaging techniques are frequently used to investigate the integration of functionally specialized brain regions in a network. Functional connectivity, which quantifies the statistical dependencies among the dynamics of simultaneously recorded signals, allows to infer the dynamical interactions of segregated brain regions. In this review we discuss how the functional connectivity patterns obtained from intracranial and scalp electroencephalographic (EEG) recordings reveal information about the dynamics of the epileptic brain and can be used to predict upcoming seizures and to localize the seizure onset zone. The added value of extracting information that is not visibly identifiable in the EEG data using functional connectivity analysis is stressed. Despite the fact that many studies have showed promising results, we must conclude that functional connectivity analysis has not made its way into clinical practice yet.